FEATURES AND SEVERITY OF THYROTOXIC ATRIAL FIBRILLATION - Bahriyeva , Nigora Naimovna; Norimov, Shaxriyor; Xurramova, Gulshan; Shodiyeva, Mashxura (Educational Research in Universal Sciences, 2024)
Atrial fibrillation (AF) is called the most serious complication of thyrotoxicosis, since it develops quite often (in 10–15% of cases) and is associated with an increased risk of mortality [1, 2]. There is evidence that patients with AF and hyperthyroidism differ from patients with AF and normal thyroid function, both clinically [3] and pathophysiologically[4]. However, there is a paucity of data describing the characteristics and outcomes of patients with thyrotoxic AF (TAF). It is also important to note the paucity of recommendations regarding treatment strategies for this group of patients [3]. Studying the features of the course of TAF and identifying predictors of its unfavorable course will provide a deeper understanding of the differences between DFT and AF of other etiologies and will help in creating more detailed recommendations for patients with TAF. When analyzing the literature, a number of studies were found that studied the relationship between clinical types of TFT, the results of which are contradictory. Some studies demonstrate the predominance of the paroxysmal type [5, 6], others - the persistent one [7, 8]. One study also examined factors associated with type of TFT: duration of thyrotoxicosis less than 1 year (odds ratio (OR) 4.3, 95% confidence interval (CI) 1.1–16.6) and lower levels of free tetraiodothyronine (OR 0.97, 95% CI 0.95–0.99) were associated with paroxysmal AF [6]. From our point of view, the characteristics of the course of TAF, in addition to the clinical type, can also include the severity of symptoms of AF and developed heart failure (HF) against the background of AF, and the ventricular contraction frequency (VFR) against the background of AF. No studies were found in the literature describing these characteristics in patients with TFT. Thus, the characteristics of the severity of TPP and the factors associated with them have not been studied enough, but their study seems important both for understanding the mechanisms of development of TPP and from a practical point of view. Among other things, this may be useful for optimizing the prevention of severe complications of this rhythm disorder.